The Sexual Grooming Model of Child Sex Trafficking - Winters, Georgia M. (Victims & offenders, 2022)
There has yet to be universally-accepted model of child sex trafficking recruitment tactics. Research suggests that child sex traffickers may use strategies to recruit and retain minors that mirror the tactics used by child abusers when sexually grooming minors. Based on a thorough review of the child sex trafficking literature and integrating it with a content validated model of child sexual grooming, we propose the Sexual Grooming Model of Child Sex Trafficking (SGM-CST), which includes five overarching stages: 1) victim selection; 2) gaining access and isolation; 3) trust development; 4) desensitization to touch; and 5) post-abuse maintenance.